2020
DOI: 10.1021/acsami.0c16241
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Daytime Radiative Cooling Devices with Simultaneous Light-Emitting and Radiative Cooling Functional Layers

Abstract: In this study, multifunctional light-emitting and passive radiative cooling (LEPC) materials and devices are designed by embedding chemically designed perovskite nanocrystals (NCs) into the radiative polymer layer. Lead halide perovskite NCs are chosen as the light-emitting material, owing to their high photon radiation rate and low phonon generation. To integrate the perovskite NCs into the radiative polymer layers, a surface passivation is achieved by coating the NCs with silica. The silica shell synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…The absorption power of 80 W/m 2 corresponds to that the radiation film has a transmittance of nearly 10%, so it is important to improve the sunlight reflection of the radiation film, otherwise the radiation film is difficult to obtain the cooling effect during the daytime. In this case, the temperature inside the test chamber was used as the environmental comparison temperature to evaluate the radiation cooling capacity in some articles [13][14][15][16]. As can be seen from figure 6 (b), for the case of 80 W/m 2 pad absorbing power, although the temperature at the center of the radiation film is greater than the external ambient temperature, it is still less than the temperature near the inner wall of the insulation chamber.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption power of 80 W/m 2 corresponds to that the radiation film has a transmittance of nearly 10%, so it is important to improve the sunlight reflection of the radiation film, otherwise the radiation film is difficult to obtain the cooling effect during the daytime. In this case, the temperature inside the test chamber was used as the environmental comparison temperature to evaluate the radiation cooling capacity in some articles [13][14][15][16]. As can be seen from figure 6 (b), for the case of 80 W/m 2 pad absorbing power, although the temperature at the center of the radiation film is greater than the external ambient temperature, it is still less than the temperature near the inner wall of the insulation chamber.…”
Section: Resultsmentioning
confidence: 99%
“…Another method to promote colored radiative cooling is integrating light emitting materials with thermal emission films. [77][78][79] Normally, the colored paints or pigments will inevitably result in solar heating. However, light-emitting materials, such as photoluminescent dyes, can partially convert the UV portion of solar irradiance into emitted light, hence slightly reducing the solar-heat conversion.…”
Section: Integration With Photoluminescencementioning
confidence: 99%
“…However, light-emitting materials, such as photoluminescent dyes, can partially convert the UV portion of solar irradiance into emitted light, hence slightly reducing the solar-heat conversion. With optimized structures, Jeon et al 78 reported colored emitters that can realize subambient cooling performance under 800 W∕m 2 solar illumination. Intriguingly, these photoluminescent films can produce vivid colors in dark environments at night [Figs.…”
Section: Integration With Photoluminescencementioning
confidence: 99%
“…The bilayer structure of polymers and metals is also widely used to maximize IR reflection and emission [57][58][59][60].…”
Section: Ir Emissivity Of Cellulose-based Radiatormentioning
confidence: 99%
“…The Si-O-Si bond has good emissivity in the range of 8-13 ”m [54][55][56]. The bilayer structure of polymers and metals is also widely used to maximize IR reflection and emission [57][58][59][60].…”
Section: Ir Emissivity Of Cellulose-based Radiatormentioning
confidence: 99%